Implementasi Metode Biosong Dalam Pembelajaran Biologi Di SMAN 6 Maros - Suci Alfiani; Pertiwi Indah Lestari; Sri Maya (CV. Insight Publisher, 2023)
This research is a quantitative study with a quasy experimental method that aims to determine whether or not there is an effect of implementation the Biosong method on improving the learning outcomes of biology students in class XI MIPA at SMAN 6 Maros. The experimental class eses conventional learning method ang the control class uses conventional learning methods. The instrument used is in the form of an essay text consisting of 5 validated questions. The data analysis technique used was descriptive analysis and hypothesis analysis in the experimental class that applied the Biosong learning method with an average of 78,00 and a standard deviation of 7,114 while the control class that applied conventional methods obtained an average value of mean 66,39 and standard deviation 15,139. Based on the result of the Mann Whitney assess the learning outcomes obtained asymp. sig (2-tailed) 0,004<0,05. It can be concluded that the implementation of the usual method has an influence on improving the learning outcomes of biology students of class XI MIPA at SMAN 6 Maros on cell material.